Methylome and transcriptome signature of bronchoalveolar cells from multiple sclerosis patients in relation to smoking. (June 2021) - Ringh, Mikael V; Hagemann-Jensen, Michael; Needhamsen, Maria; Kullberg, Susanna; Wahlström, Jan; Grunewald, Johan; Brynedal, Boel; Jagodic, Maja; Ekström, Tomas J; Öckinger, Johan; Kular, Lara
Background: Despite compelling evidence that cigarette smoking impacts the risk of developing multiple sclerosis (MS), little is known about smoking-associated changes in the primary exposed lung cells of patients. Objectives: We aimed to examine molecular changes occurring in bronchoalveolar lavage (BAL) cells from MS patients in relation to smoking and in comparison to healthy controls (HCs). Methods: We profiled DNA methylation in BAL cells from female MS ( n = 17) and HC ( n = 22) individuals, using Illumina Infinium EPIC and performed RNA-sequencing in non-smokers. Results: The most prominent changes were found in relation to smoking, with 1376 CpG sites (adjusted P < 0.05) differing between MS smokers and non-smokers. Approximately 30% of the affected genes overlapped with smoking-associated changes in HC, leading to a strong common smoking signature in both MS and HC after gene ontology analysis. Smoking in MS patients resulted in additional discrete changes related to neuronal processes. Methylome and transcriptome analyses in non-smokers suggest that BAL cells from MS patients display very subtle (not reaching adjusted P < 0.05) but concordant changes in genes connected to reduced transcriptional/translational processes and enhanced cellular motility. Conclusions: Our study provides insights into the impact of smoking on lung inflammation and immunopathogenesis of MS.